ALTERNATIF PERENCANAAN SUPER STRUCTURE JEMBATAN RANGKA BAJA PADA JEMBATAN WAY UMALOYA DI KABUPATEN KEPULAUAN SULA - Mardhan Fatmona; Erwinsyah Tuhuteru; Muhammad Taufiq Yuda Saputra (Journal of Science and Engineering, 2022)
The Way Umaloya Bridge in the Sula Islands Regency is a reinforced concrete girder type bridge which has a total bridge span length of 60.00 with field survey results there are cracks in each of the longitudinal and transverse girders, corrosion of steel reinforcement and deflection due to repeated loads. The purpose of this research is as a planning alternative to analyze the dimensions of each element of the superstructure of the steel frame bridge in the redesign. In planning the superstructure of the steel truss bridge, warren truss type is used with analysis and design calculations using the LRFD method for control of the steel frame, such as tensile bars, compression rods, bending rods and bolted connections. In each calculation, the superstructure elements are controlled against the requirements for selecting the profile dimensions and controlled for materials and stresses. In planning the super structure of the bridge, the results of the analysis and design were obtained as follows: the use of dimensions and reinforcement on the pavement floor plate and vehicle floor plate used the dimensions of the pavement floor plate 25 x 50 x 6000 cm, with the main reinforcement requirements ø 16-12 mm and reinforcement for ø 12-200 mm, vehicle floor plate dimensions are used 20 x 600 x 6000 cm, with the need for basic reinforcement ø 16-100 mm, reinforcement for ø 12-200, the use of longitudinal girders with dimensions of WF profile 450 x 200 x 9 x 14 mm , the use of transverse girders with a WF profile dimension of 800 x 300 x 14 x 26 mm, the use of a main frame with a WF profile dimension of 400 x 400 x 45 x 70 mm, the use of wind ties with a WF profile dimension of 150 x 150 x 7 x 10 mm, the use of connection on the node plate with a plate thickness of 2.5 cm, the use of connecting plate connections between longitudinal girders, transverse girders, and the main frame with a profile dimension of L 100.100.10 mm. and the use of connection plates on wind ties with a dimension of 1.0 cm thick C profile.